2012
DOI: 10.1371/journal.pone.0045552
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Wool δ13C Reveals No Effect of Grazing on the C3/C4 Ratio of Vegetation in the Inner Mongolia–Mongolia Border Region Grasslands

Abstract: We tested whether the abundance of C4 vegetation in grasslands of the Mongolian plateau is influenced by grazing conditions. The analysis exploited the politically originated contrast that exists between Mongolia (low stocking rate, transhumant system) and the district of Inner Mongolia, China (high stocking rate, sedentary system). We estimated the proportion of C4 carbon (PC4) in grazed vegetation from the relative carbon isotope ratio (δ13C) of sheep wool sampled from 298 annual shearings originating from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…4), but Mongolia’s Gobi–Steppe ecosystem still remains one of the largest intact expanses of steppe, desert-steppe and desert habitats in the world 12 . There is also little evidence that C 3 /C 4 plant ratios are influenced by grazing pressure 29 and the fact that diets in historic and extant khulan were almost identical further argues against a habitat-induced diet change in Przewalski’s horses.
Figure 4Living conditions of Przewalski’s horses and khulan in the steppe and desert steppe areas of Mongolia in winter past and present. For supporting references see Supplementary Information S5.
…”
Section: Discussionmentioning
confidence: 99%
“…4), but Mongolia’s Gobi–Steppe ecosystem still remains one of the largest intact expanses of steppe, desert-steppe and desert habitats in the world 12 . There is also little evidence that C 3 /C 4 plant ratios are influenced by grazing pressure 29 and the fact that diets in historic and extant khulan were almost identical further argues against a habitat-induced diet change in Przewalski’s horses.
Figure 4Living conditions of Przewalski’s horses and khulan in the steppe and desert steppe areas of Mongolia in winter past and present. For supporting references see Supplementary Information S5.
…”
Section: Discussionmentioning
confidence: 99%
“…While C 4 plants make up a relatively limited portion of the biotic community today, we established local isotopic baselines for Mongolia in the past using archaeological fauna in order to determine if shifts in δ 13 C values through time are the product of environmental variations or social and economic choices. Isotopic studies of modern and archaeological herd animals have shown differences in δ 13 C values between more and less arid regions [43][44][45] , and that there is variation in the availability of C 3 and C 4 plants across the country 46,47 . While there were no fauna associated with the human remains collected for this study, we were able to use previously published faunal stable isotope data from the Minusinsk Basin of Siberia (just north of Mongolia)(MNSK, AD, AM; n = 21) 20,29 , the Gobi (BGC; n = 14) 30,48 , Gobi-Altai (SBR; n = 5) 30 , and north central Mongolia (EG; n = 13) 30 areas to show that regional herbivores generally consumed C 3 plants, with some having higher stable carbon isotope values, indicative of C 4 plant consumption, in the hyper-arid desert regions 30,48 .…”
Section: Environmental Differencesmentioning
confidence: 99%
“…After harvest of maize, roe deer must feed from plants using the C3 photosynthetic pathway. The large contrast in carbon isotopes between C4 and C3 plants (about 14‰ [23]) is recorded in the animal tissue [5,8]. δ 13 C in keratinous tissue thus increases from about −26‰ with pure C3 diet to −12‰ with pure maize diet, which includes enrichment by 2.7‰ due to the diet-keratin shift [21].…”
Section: Introductionmentioning
confidence: 99%
“…Such heterogeneities can especially be expected for herbaceous species or young trees occupying niches. Stored animal tissues like wool products or hunting trophies provide long-term time series [8] but may also be used to resolve within growing periods [9].…”
Section: Introductionmentioning
confidence: 99%